Macroscopic anatomy of the thymus arteries and veins the during the foetal stage in the alpaca - Melgarejo H., Rafael (2023)
The aim of this study was to know the macroscopic arterial and venous anatomy of the thymus in alpaca foetuses. Ten foetuses were used with gestational ages between 107 and 278 days obtained in the local slaughterhouse (Huancavelica, Peru), and processed to perform the anatomical technique of vascular filling. An aqueous solution of acrylic resin and red Chinese ink was injected into a cannulated umbilical artery, and another aqueous solution of acrylic resin and blue Chinese ink was injected into a cannulated umbilical vein. The foetuses were preserved in 10% formalin while the resin solidified. The foetuses were dissected. The thymus was lobed and formed by the right cranial cervical thymus, left cranial cervical thymus, caudal cervical thymus, intermediate thymus, and thoracic thymus. The right and left common carotid arteries, the right and left cranial thyroid arteries and the right and left caudal thyroid arteries emitted arterial branches to the cervical thymus, while the aortic arch, brachiocephalic trunk, and left subclavian artery emitted arterial branches to the thoracic thymus. The right and left external jugular veins emitted venous branches to the cervical thymus, and the left cranial vein and the left costocervical vein emitted venous branches into the thoracic thymus. No blood vessels emitted arterial branches and venous branches towards the intermediate thymus.